Gifted children of color around the world diverse needs, exemplary practices and directions for the future. - Davis, Joy Lawson, 1953-; Moore, James L., III; Lewis, Chance W. (Chance Wayne), 1972- (Advances in race and ethnicity in education ;, 2016)
We live in a global society, wherein our dependence on our neighbors is growing more intensely each year. Technology, travel, and interdependent economic systems require that nations know more and share more of their natural resources. Among the most precious of these resources is the intellectual talent that resides in their countries. This edited volume sheds light on the unique challenges, trends, and intersecting issues related to identifying intellectual potential of children of color around the world, providing access to appropriate curriculum and instructional opportunities, addressing the professional capacities of teachers working with these students, and the role of diverse families and communities in the talent development process in these communities. To achieve the volume's objectives, the editors bring together expert scholars from around the world who have a vested interest in gifted children of color.